2013
DOI: 10.1007/s12028-013-9847-9
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Monitoring ICP in Neurocritical Care: Results from a National Practice Survey

Abstract: The results highlight the need to develop standardized approaches to measuring, monitoring, recording, and treating ICP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 24 publications
0
17
1
3
Order By: Relevance
“…Although normal CT brain findings have low incidence of ICP elevation in TBI, a subset population of TBI patients with age over 40, systolic blood pressure under 90 mmHg, and clinical evidence of posturing require ICP monitoring regardless of CT findings [2, 4]. Evidence for improved outcomes with continuous ICP monitoring has been varied [6, 7••, 8, 9] leading to subsequent variability of ICP monitoring practices amongst various NICU centers [10, 11]. The most recent MMM guidelines have subsequently been formed to provide expert consensus on the use of these monitoring modalities and a more congruent practice amongst difference centers.…”
Section: Intracranial Pressurementioning
confidence: 99%
“…Although normal CT brain findings have low incidence of ICP elevation in TBI, a subset population of TBI patients with age over 40, systolic blood pressure under 90 mmHg, and clinical evidence of posturing require ICP monitoring regardless of CT findings [2, 4]. Evidence for improved outcomes with continuous ICP monitoring has been varied [6, 7••, 8, 9] leading to subsequent variability of ICP monitoring practices amongst various NICU centers [10, 11]. The most recent MMM guidelines have subsequently been formed to provide expert consensus on the use of these monitoring modalities and a more congruent practice amongst difference centers.…”
Section: Intracranial Pressurementioning
confidence: 99%
“…42 Studies have demonstrated that when ICP is unresponsive to medical therapy, there is an increase in poor outcome. [43][44][45][46][47][48][49] Recent literature has begun to question the practice variation in ICP monitoring, 50,51 and the optimal target for interventions aimed to treat ICP. 52…”
Section: Intracranial Pressurementioning
confidence: 99%
“…2 The ICP monitoring techniques evolved from invasive to noninvasive, both with their limitations and advantages. The invasive method is characterized as a procedure in which a catheter is inserted in the intraventricular, subarachnoid or intraparenchymal region, which may expose the patient to risks of precipitation of intracranial hematoma, aggravated cerebral edema, damage to the parenchyma, intracerebral hemorrhage and infection.…”
Section: Introductionmentioning
confidence: 99%